Cintilografia miocárdica de perfusão com Tc-99m sestamibi empacientes com forma crônica indeterminada da doença de Chagas - Ivana Moura Abuhid (2011)
Chagas disease is characterized by an acute phase during about two months followed by a chronic phase that endures for the rest of the hosts life. Each year, approximately 2% to 5% of the patients evolve, from the indeterminate form to either clinical cardiac or digestive form. Also, from 5 to 10 years of development, a third of the patients with chronic indeterminate form (FCI) can become cardiopatic and approximately 50% of the patients remain FCIs indefinitely. Although several complementary non invasive exams like the echocardiogram, Holter, ergometric test, brain natriuretic peptide dosage, autonomic activity tests, among others have been done in chagasic patients the role of the myocardial scintigraphy at rest and after stress has not been well established during this phase of the disease. In this work, 18 patients carrying the indeterminate form of the Chagas disease and an equal number of normal controls matched by gender and age were subjected to myocardial scintigraphy at rest and after stress with 99mTc sestamibi aiming at detecting early cardiac lesions. The results did not show perfusion abnormalities or radiotracer distribution damages in patients carrying the indeterminate phase of the Chagas Disease , although one patient presented with left ventricular disfunction evaluated by this method. This study results, considering the small number of patients, show that myocardial scintigraphy at rest and after stress with 99mTc sestamibi is not an effective method to detect early myocardial alterations in the indeterminate form of the Chagas disease.